Immediate effects of myofascial release on neuromechanical characteristics in female and male patients with low back pain and healthy controls as assessed by tensiomyography. A controlled matched-pair study - Lohr, Christine; Medina-Porqueres, Iván (Elsevier, 2021)
Background: Low back pain (LBP) is a major health issue in most industrialised countries. Lumbodorsal fascia has been advocated as a potential source of pain in the lumbopelvic region. Myofascial release constitutes a manual therapeutic approach focussing on the restoration of altered soft tissue function. No previous study has focused on quantifying neuromechanical effects of myofascial release on LBP patients through tensiomyo- graphy . The purpose of this study was to quantify immediate neuromechanical alterations of myofascial re- lease on patients with LBP and healthy controls through tensiomyography parameters. Methods: The participants' (n = 30) bilateral lumbar erector spinae muscles were assessed via ten- siomyography before and after a 6-min myofascial release treatment of the lumbodorsal fascia to evaluate the muscles' mechanical characteristics. Subjects with LBP (n = 15) were eligible to partake if they re- ported having had LBP for most days in the past 12 weeks. Muscle displacement (Dm [mm]), velocity of contraction (Vc [mm/s]), and lateral symmetry (Ls [%]) were assessed through tensiomyography testing. Findings: Statistical analyses revealed a significant increase for velocity of contraction in the right (p = .021) and left (p = .041) lumbar erector spinae for the subjects with LBP but not for the healthy controls (both p > .14). Interpretation: We suggested that myofascial release alters neuromechanical characteristics in subjects with LBP. Tensiomyography may be implemented in clinical settings to monitor intervention effects of the myofas- cial system, especially the tensiomyography parameter velocity of contraction.
Keywords: Lumbalgia - Fisioterapia; Lumbalgia - Tratamiento; Mechanomyography; Back pain; Fascia thoracolumbalis; Myofascial induction; Muscle contraction; Fascia